Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Review - Page 407: 128



Work Step by Step

$(2x^{-4}y^{3})^{-4}=$ $(2)^{-4}(x^{-4})^{-4}(y^{3})^{-4}=$ $(2)^{-4}(x)^{16}(y)^{-12}=$ $\frac{(x)^{16}}{(2)^{4}\times y^{12}}=$ $\frac{x^{16}}{16\times y^{12}}=$ $\frac{x^{16}}{16y^{12}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.